(untitled) (Experimental biology, 2015)
Insufficiently high plasticity in Kazakhstan cultivated varieties and triticale breeding forms associated with limited genetic diversity of the starting material. Expansion of the species diversity of winter crops is one of the necessary conditions stabilize grain production. In conventional breeding to create varieties of triticale takes an average of 10-12 years. Much of this time (5-6 years) is spent on the creation of homozygous lines. Modern cell biotechnology can reduce this period to almost 1 year. Cellular Biotechnology (selection in vitro, embryo culture, haploids in anther culture, micro propagation) is widely used in the creation of the starting material. Allows the use of biotechnology to make the selection process aimed, accelerate time to create new forms of desirable characteristics, adapted to the specific conditions of cultivation. Also for improving the efficiency of selection in vitro and in vivo, it is important to identify the early stages of the individual differences of the new source of breeding material from the forms. Keywords: